Icariin-loaded composite scaffold promotes osteogenic differentiation and bone regeneration - Dong-Sheng Jin; Zhang-Hong Zhao; Shi-Qiang Ruan; Wen-Liang Huang; Ren-Yuan Tian; Yu Wan; Jiang Deng (BMC Musculoskeletal Disorders)
Abstract Background Bone defects remain a significant challenge in orthopedics, and traditional treatments often face limitations. Icariin (ICA) has been shown to promote osteogenic differentiation and angiogenesis, which may benefit bone repair. Methods ICA-loaded microspheres were prepared using an evaporation method with a co-solvent system. The encapsulation efficiency, drug loading, and release characteristics were evaluated. Silk fibroin/chitosan/nano-hydroxyapatite (SF/CS/nHA) composite scaffolds incorporated with ICA microspheres were fabricated using vacuum freeze-drying. Bone marrow mesenchymal stem cells (BMSCs) were cultured on these scaffolds in vitro. Scanning electron microscopy (SEM) was used to observe the morphology of microspheres and scaffolds, as well as cell adhesion. In vitro assessments of BMSC morphology, proliferation, and migration on different scaffolds were conducted using CCK-8 assays, live/dead staining, and scratch tests. Osteogenic differentiation was evaluated by alkaline phosphatase staining, Alizarin Red staining, immunofluorescence, RT-qPCR, and Western blotting. A rabbit radial critical-size bone defect model was established in vivo, and SF/CS/nHA-ICA composite scaffolds were implanted at the defect sites. Bone repair effects were assessed by CT imaging, hematoxylin-eosin (H&E) staining, and Masson’s trichrome staining. Osteogenic and angiogenic protein expression levels were further analyzed by immunohistochemistry and Western blot. Results In vitro experiments demonstrated that the SF/CS/nHA-ICA group had superior BMSC adhesion, cell morphology, proliferation, and osteogenic differentiation compared to other groups (P < 0.05). In vivo, evaluations indicated that the addition of ICA significantly enhanced bone regeneration and vascularization at the defect sites compared to control and other experimental groups. Western blot and immunohistochemical analyses confirmed significant upregulation of osteogenic and angiogenic proteins (type I collagen, runt-related transcription factor 2, osteocalcin, vascular endothelial growth factor) in the SF/CS/nHA-BMSCs-ICA group. Conclusion ICA-loaded scaffolds effectively promote bone regeneration and repair of bone defects, offering a potential strategy for the treatment of bone defects.